Gram‐negative bacterial toe web infection – a systematic review. (7th November 2017) - Weidner, T.; Tittelbach, J.; Illing, T.; Elsner, P.
Abstract: Gram‐negative bacterial toe web infection (GNBTWI) is a frequent therapeutic challenge in clinical practice with high recurrence rates and frequent need of systemic drugs. The aim of this systematic review was to provide an updated overview and evidence‐based data on pathogens, risk factors and treatment of GNBTWI along with promoting a consistent international terminology. This systematic review is based on a search in PubMed database for English and German articles published between 1980 and 2016. A total of seven articles were considered appropriate for inclusion in this review regarding to treatment and outcome. Throughout the medical literature, a variety of terms for bacterial toe web infections is used. Only few data on the incidence of GNBTWI were published. GNBTWI has been shown to have a significant male predominance. Pseudomonas aeruginosa is the most commonly identified organism beside a high mixed infection rate. We identified the following predisposing factors: interdigital tinea, occlusion and humidity, history of self‐medication with antifungals, antibiotics and glucocorticosteroids. As for treatment, debridement of macerated skin lesions and the hyperkeratotic rim showed good response in three published cases. Bacteriological workup of swabs including an antibiogram is recommended for identification of the proper topical and systemic therapy. Autosensitization dermatitis and frequent recurrences are common complications of GNBTWI. Despite the fact, that GNBTWI is an accepted disease entity, scarce data on GNBTWI exist in the medical literature. Randomized controlled trials are missing although needed for evidence‐based therapy. To facilitate communication and exchange of updates of GNBTWI, we promote the suggested terminology for bacterial toe web diseases.